Cost/effectiveness analysis of atorvastatin in patients with acute coronary syndromes - Cammarota, Simona; Menditto, Enrica; Putignano, Daria; Citarella, Anna (Farmeconomia. Health Economics and Therapeutic Pathways, 2010)
Introduction: recent clinical trials found that high-dose statin therapy, compared with conventional-dose statin therapy, reduces the risk of cardiovascular events in patients with acute coronary syndromes (ACS) and stable coronary artery disease (CAD). With the introduction of simvastatin and pravastatin generics and the next patent expiration of atorvastatin, projected for 2011 in Italy, it is natural to ask: what is the most cost-effective treatment for a rational use of resources?Aim: the aim of this study was to estimate the cost-effectiveness of high-dose atorvastatin versus conventional standard-dose statins based on the scenario of atovastatin price evolution.Methods: a cost-effectiveness analysis was conducted in the perspective of the Italian National Health Service over the 4.9 years time horizon. Clinical data were obtained from a pooled analyses of the 3 clinical trials that directly compared high-dose atorvastatin with conventional standard-dose statins in patients with either ACS or CAD. Hospitalizations were quantified based on the Italian National Health Service tariffs and drug costs according to the Italian National Therapeutic Formulary (2009). Assuming the cost of atorvastatin reduces in line with that observed for simvastatin when the patent expires, 3 scenarios were constructed: atorvastatin current price (scenario 1); 55% price discount (scenario 2); 65% price discount (scenario 3). Effects were measured in terms of primary composite endpoint (coronary death or any adverse cardiovascular event). All costs were discounted at 3% per annum. Sensitivity analyses were performed to assess the robustness of findings. Results: intensive therapy with atorvastatin provided a hospitalization cost saving of 245,519.36 € per 1,000 patients. Under the assumptions established for scenario 1 and scenario 2, the incremental cost-effectiveness of treatment with atorvastatin 80 mg was estimated to be 20,289.72 € and 917.05 € for patient free from event, respectively; it was cost-saving for the scenario 3. Conclusions: high-dose atorvastatin represented a cost-effective use of healthcare resources in Italy. If the cost of atorvastatin reduces by 65% when the patent expires, for every million patient with SCA or CAD stable, treated for 5 years, the high-dose atorvastatin strategy potentially yields a cost-saving of ~2,4 billion € for the NHS.